2014
DOI: 10.1128/ec.00017-14
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Validation of Aminoacyl-tRNA Synthetases as Drug Targets in Trypanosoma brucei

Abstract: bHuman African trypanosomiasis (HAT) is an important public health threat in sub-Saharan Africa. Current drugs are unsatisfactory, and new drugs are being sought. Few validated enzyme targets are available to support drug discovery efforts, so our goal was to obtain essentiality data on genes with proven utility as drug targets. Aminoacyl-tRNA synthetases (aaRSs) are known drug targets for bacterial and fungal pathogens and are required for protein synthesis. Here we survey the essentiality of eight Trypanosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 77 publications
(82 reference statements)
1
32
1
Order By: Relevance
“…The development of target-based inhibitors is an attractive approach for addressing some of these concerns; however, few targets have been validated in T. cruzi or Leishmania due to their limited genetic tractability. Advances in T. brucei genetics have allowed genome-wide gene essentiality screens and the validation of new targets and chemotypes for the development of novel drugs (Alsford, et al, 2011; Cestari and Stuart, 2013; Kalidas, et al, 2014). Since the genomes of these parasites are highly conserved (~94% synteny and ~60% overall identity of orthologous genes) (El-Sayed, et al, 2005), the identification of new targets and discovery of T. brucei -specific inhibitors may be useful for chemical validation of orthologous enzymes in T. cruzi and Leishmania sp .…”
Section: Introductionmentioning
confidence: 99%
“…The development of target-based inhibitors is an attractive approach for addressing some of these concerns; however, few targets have been validated in T. cruzi or Leishmania due to their limited genetic tractability. Advances in T. brucei genetics have allowed genome-wide gene essentiality screens and the validation of new targets and chemotypes for the development of novel drugs (Alsford, et al, 2011; Cestari and Stuart, 2013; Kalidas, et al, 2014). Since the genomes of these parasites are highly conserved (~94% synteny and ~60% overall identity of orthologous genes) (El-Sayed, et al, 2005), the identification of new targets and discovery of T. brucei -specific inhibitors may be useful for chemical validation of orthologous enzymes in T. cruzi and Leishmania sp .…”
Section: Introductionmentioning
confidence: 99%
“…The borrelidins have attracted significant attention from the natural products community, and their noteworthy anti‐infective and cytotoxic activities have especially drawn the interest and efforts of biosynthetic and chemical synthesis researchers . In this study, three new borrelidins ( 1 – 3 ), along with four previously reported family members ( 4 – 7 ), were isolated from a likely associated symbiont S. olivaceus SCSIO LO13 from the marine pulmonated mollusk Onchidium sp.…”
Section: Discussionmentioning
confidence: 88%
“…Borrelidin A ( 4 ) was the first member of the family discovered and has been shown to have antibiotic and antimalarial activities as well as the ability to inhibit tumorigenic and angiogenic processes . Borrelidin A ( 4 ) has been particularly important in demonstrating the importance of threonyl tRNA synthetase (ThrRS) inhibition as a viable means of targeting the causative agent for malaria . Although borrelidin A ( 4 ) is toxic to non‐malignant cell types, its antitumor potential, as reflected in part by its ability to inhibit the growth of hepatocellular carcinoma cells, has garnered a significant amount of clinical interest .…”
Section: Introductionmentioning
confidence: 99%
“…2 and 3) after exposure to lapatinib. Trypanosome rounding has been observed in knockdown of proteins that are also involved in endocytosis (39), protein synthesis (40), and cell cycle (41,42). Trypanosomes have a subpellicular microtubule array (corset) that would need to be reorganized during cell rounding.…”
Section: Discussionmentioning
confidence: 99%